The End of Resilience? Managing Vulnerability Through Temporal Resourcing and Resisting. (May 2023) - Branzei, Oana; Fathallah, Ramzi
We induce a first-person conceptualization of entrepreneurial resilience. Our seven-year, two-study ethnography shows that entrepreneurs enact resilience as a four-step process of managing vulnerability: they richly experience episodes of adversity, self-monitor across episodes, reassess personal thresholds and reconcile challenges with coping skills. Entrepreneurs manage vulnerability by (1) modifying ( stretching and shrinking ) objective time and (2) changing their subjective experience of time as working with or against the clock through temporal resourcing or temporal resisting . We extend the theory and practice of entrepreneurial resilience by elaborating the interplay of objective and subjective time in managing vulnerability in recurrent and unprecedented crises.